Bipedal in-shoe kinetics of skateboarding - the ollie - Leuchanka, A.; Ewen, J.; Cooper, B. (Footwear Science, 2017)
Skateboarding is a globally participated and popular sport with a reported participation of over 11 million in the United States alone (SGMA, 2007). Published epidemiological studies have stated the significant incidence of musculoskeletal injuries associated with skateboarding (Frederick, Determan, Whittlesey, & Hamill, 2006). The inherent nature of skateboarding makes it difficult to quantify using standard laboratory methods. In-field protocols have been attempted to quantify the metabolic demands of the activity, while only partial segments of a given movement have been quantified from a biomechanics perspective (Frederick et al., 2006; Hetzler, Hunt, Stickley, & Kimura, 2011). Therefore, unique methods of testing are necessary to develop a complete understanding behind the basic movements of skateboarding.